Covid-19 and spatial planning: A few issues concerning public policy - Lai, Sabrina; Leone, Federica; Zoppi, Corrado (TeMA - Journal of Land Use, Mobility and Environment, 2020)
This article analyzes some relevant questions as regards the impact of COVID-19-related social living conditions on spatial planning policies and practices. The proposed discussion aims at highlighting and discussing a number of outstanding topics of spatial planning which public administrative bodies, practitioners, entrepreneurs and organizations operating in the profit and non-profit sectors, and the local communities should carefully consider with reference to a new planning outset after the lockdown period. Innovative and creative approaches should be identified and implemented when dealing with collective public spaces, shopping malls, retail activities and related areas, urban and regional mobility-related infrastructure and services, food-supply changes and their implications in terms of development of local food-producing practices, spatial social control and privacy, mitigation of climate change-related negative impacts, and public awareness and commitment towards losers, especially urban losers. Each of these points presents important challenges for the future of spatial planning. Some of these challenges are synthetically described and discussed in this article.